2022
DOI: 10.3390/ijerph19031193
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication Perceptions and Practice of Medical and Pharmacy Students in Serbia

Abstract: Background. Attitudes towards conventional and complementary medicine among future healthcare professionals can impact their future pharmacotherapy practice. This study aimed to determine the prevalence and predisposing factors related to self-medication among medical and pharmacy students. Methods. This cross-sectional questionnaire-based study was performed at the Faculty of Medicine, University of Novi Sad, Serbia, on first- and final-year students of medicine and pharmacy. The multivariate Poisson regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
3
5
0
1
Order By: Relevance
“…In our study, the overall prevalence of SM was found to be as high as 81.6%, similar to the findings of Tomas Petrović et al [11], and Ramadan [12]. It was slightly higher than the findings of Khadka et al…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the overall prevalence of SM was found to be as high as 81.6%, similar to the findings of Tomas Petrović et al [11], and Ramadan [12]. It was slightly higher than the findings of Khadka et al…”
Section: Discussionsupporting
confidence: 90%
“…Sources of obtaining medicines were pharmacy shops (78.8%) and leftovers at home/hostel (39.1%), which is somewhat similar to the findings in Tomas Petrović et al [11], Zeru et al [4], and in Shrestha et al [18].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Khatony et al (17) dentro de su estudio cualitativo documentaron como consecuencias positivas de la automedicación de acuerdo a estudiantes de enfermería al ahorro de tiempo, que concuerda con uno de https://doi.org/10.56294/saludcyt2023312 5…”
Section: Discussionunclassified
“…On the other hand, irresponsible or irrational self-medication, typically with prescription-only medications, increases the chances of direct harm to the patient in the form of adverse drug reactions (Albusalih.,2017). However, even when used responsibly, Self-medication is associated with several dangers and risks for the community such as a delay in diagnosis and incorrect diagnosis, the occurrence of druginduced diseases, and the growth of public health expenditure (Tomas Petrović et al,2022).…”
Section: Challenges Related To Self-medication Practicesmentioning
confidence: 99%